155 A cross-sectional study of low back pain among retired international athletes (runners, swimmers, rowers, and hockey players). (3rd March 2020) - Cooper, Dale; Palmer, Debbie; O'Hanlon, Mary; Batt, Mark
Abstract : Background: Prevention of low back pain (LBP) requires the identification of modifiable risk factors. Currently there is limited evidence of these risk factors in current and retired athletic populations. Objective: To determine the prevalence and factors associated with LBP among retired international athletes (runners, swimmers, rowers, and hockey players). Design: Cross-sectional survey. Patients (or Participants): 323 retired international level athletes, aged 30–97 years (median age 62 years), 43% female ( n =139) who had competed internationally for Great Britain. Interventions (or assessment of risk factors): Data was collected on age (years), sex, height (cm), weight (kg), sport and occupational history, bodily pain, training load, joint flexibility and medical history. A prior injury to the lumbar spine was defined by an injury causing pain > 30 days and requiring medical attention. Main outcome measurements: LBP (with or without leg pain) on most days of the past one-month. Results: Overall, the prevalence of LBP was 26.0% (84/323). The prevalence of LBP was 24.1% (21/87) in rowers, 29.2% (35/120) in runners, 31.3% (20/64) in swimmers, and 15.4% (8/52) in hockey players. The odds ratio for LBP increased with a prior significant lumbar spine injury [OR 2.64; 95% CI, 1.43–4.89, p=0.002], overweight BMI [OR 1.91; 95% CI, 1.11–3.30, p=0.02], and was less prevalent among those aged 70 years and older [OR 2.37; 95% CI, 1.02–5.54, p=0.046]. No association was detected between LBP and female sex, a high training load, sporting discipline, heavy occupation post sports career, lumbar spine flexion, or comorbidities (i.e. diabetes, cancer, lung disease, stroke, heart disease). Conclusions: A prior significant lumbar spine injury and increased body mass index were associated with LBP in retired international athletes. Longitudinal follow-up is needed to determine if modification of these factors reduces the occurrence of LBP.